Exploring the Influence of Madura Etnoparenting on Social Intelligence Development in Early Childhood: A Case Study - Dwi Aprilia, Winda; Fadjryana Fitroh, Siti; Abdul Latif, Muhammad; Yuandana, Tarich (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: Ethnoparenting is a parenting model shaped by cultural values embraced by a community. In Madura, ethnoparenting plays a crucial role in nurturing children's character and social intelligence from an early age. Traditional Madurese parenting emphasizes togetherness, mutual cooperation, respect, and discipline within both family and community settings. Aims and scope of paper: This study aims to explore how the values embedded in Madurese ethnoparenting contribute to the development of children’s social intelligence. It focuses on the application of cultural practices in early childhood upbringing and their implications for interpersonal and social competencies. Methods: This study employed a qualitative ethnographic approach to explore Madurese parenting practices in fostering early childhood social intelligence. Data were collected through observations, semi-structured interviews, and document analysis involving parents and educators from various early childhood education centers in Bangkalan. The data were analyzed using reduction, display, and conclusion drawing to identify cultural patterns and parenting strategies that support social intelligence development. Results: The findings indicate that Madurese ethnoparenting fosters multiple dimensions of social intelligence in early childhood, including communication skills, empathy, cooperation, politeness, adaptability, and a sense of social responsibility. These attributes are instilled through daily routines and interpersonal interactions within both familial and communal settings. Contribution: This study underscores the pivotal role of culturally informed parenting practices in cultivating socially competent children. It emphasizes the value of preserving and adapting Madurese ethnoparenting traditions in modern parenting contexts. By highlighting the connection between culture and child development, the research contributes to broader discussions on culturally responsive parenting and early childhood education.